In Hospital Outcomes of Coronary Artery Bypass Grafting: A Gender Based Comparative Cross Sectional Study - Abrar Hussain, Usman Javed Iqbal, Muhammad Ijaz Bhatti, M. Imran Hanif, Hassan Abbas Abdullah, Namra Iqbal, Nazia Karamat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to compare the in hospital outcome of coronary artery bypass grafting in male versus female. Methodology: The cross sectional comparative study was conducted in a tertiary care setting. Using non probability sampling a calculated sample of 100 patients (50 males and 50 females) undergoing CABG were enrolled. After getting their informed consent, preoperative, intraoperative and postoperative variables were entered in the predesigned performa and the patients were observed for the difference in mortality and morbidity in both groups during hospital stay. Results: In this study 50 male and 50 females were enrolled with mean age of 54.21±8.03 years. Pulmonary complications were the most common (14%) following postoperative wound infection (12%), atrial fibrillation (10%), low cardiac output syndrome (5%), renal failure (4%), neurologic complications (4%), postoperative MI (4%) and stroke (1%). No complication other than postoperative wound infection was found statistically significant. Conclusion: Through this study we found no significant difference in in-hospital outcome. Only post-operative infection was significantly higher in female cases than male. Hence, the perception regarding in hospital outcome doesn’t relate to gender in current study.